Unilateral Termination of Construction Contract - A Comparative Study between Chinese Law and UAE Law - Yin, Zhe (2015)
Construction contract is a legal binder of the contracting parties for a certain project and there are also many industries and other parties linking to such project behind the contract. To terminate the contract will definitely affect, firstly, the contracting parties and sequentially the indirect involvers such as the manufacturers and suppliers; whereas to terminate unilaterally would even render a worse situation. So it is important for the contracting parties to fully understand the embedded unilateral termination mechanisms in their contract; this dissertation aims to achieve this point by a thorough examination to the laws, the legal and industrial publications and the standard contracts including the ones for undergoing projects to illustrate entire pictures of the unilateral termination in China and UAE. Emphasis will be also given to the application of the change of circumstance since it is found significantly remarkable and different in both countries under certain situations. Also, the most important part of this dissertation is the comparison of the unilateral terminations between China and UAE to contrast and then to demonstrate the relative advantages and common recognitions.